PENGARUH KEBIJAKAN DIVIDEN, LEVERAGE, DAN FIRM SIZE TERHADAP VOLATILITAS HARGA SAHAM - Alimuary, Farrasazahra Devina; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to determine and analyze the effect of dividend policy, Leverage, and Firm Size on stock price volatility. The research method used was purposive sampling with a total sample of 18 companies listed on the LQ-45 index listed on the Indonesia Stock Exchange (IDX). This research was conducted using secondary data on observations in 2018-2020. Data processing in this research using Microsoft Office 365 software and IBM SPSS Statistics V25.0. The results showed that Dividend Yield, Dividend Payout Ratio and Firm Size did not have a significant effect on Stock Price Volatility, while Leverage had a significant and negative effect on Stock Price Volatility. The implication of this research is the need to know what are the factors that can affect the stock price volatility which will give a good or bad signal to investors in carrying out their investment activities.